Myxoid glioneuronal tumor, PDGFRA p.K385‐mutant: clinical, radiologic, and histopathologic features. (6th November 2019) - Lucas, Calixto‐Hope G.; Villanueva‐Meyer, Javier E.; Whipple, Nicholas; Oberheim Bush, Nancy Ann; Cooney, Tabitha; Chang, Susan; McDermott, Michael; Berger, Mitchel; Cham, Elaine; Sun, Peter P.; Putnam, Angelica; Zhou, Hong; et al.
Abstract: "Myxoid glioneuronal tumor, PDGFRA p.K385‐mutant" is a recently described tumor entity of the central nervous system with a predilection for origin in the septum pellucidum and a defining dinucleotide mutation at codon 385 of the PDGFRA oncogene replacing lysine with either leucine or isoleucine (p.K385L/I). Clinical outcomes and optimal treatment for this new tumor entity have yet to be defined. Here, we report a comprehensive clinical, radiologic, and histopathologic assessment of eight cases. In addition to its stereotypic location in the septum pellucidum, we identify that this tumor can also occur in the corpus callosum and periventricular white matter of the lateral ventricle. Tumors centered in the septum pellucidum uniformly were associated with obstructive hydrocephalus, whereas tumors centered in the corpus callosum and periventricular white matter did not demonstrate hydrocephalus. While multiple patients were found to have ventricular dissemination or local recurrence/progression, all patients in this series remain alive at last clinical follow‐up despite only biopsy or subtotal resection without adjuvant therapy in most cases. Our study further supports "myxoid glioneuronal tumor, PDGFRA p.K385‐mutant" as a distinct CNS tumor entity and expands the spectrum of clinicopathologic and radiologic features of this neoplasm.